RETRACTED: Liquid crystal cell as a model of a biological system: biosensor - Denisova Olga; Abramishvili Yaroslava (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001